Stereotypes, Desires, and Constructions - Oshima, David Y. (Proceedings of Sinn und Bedeutung, 2019)
This paper develops a semantic analysis of the three constructions: (i) the subjectoriented adverb construction (Wisely, John left early), (ii) the 'Adj. + to Inf.' construction (John was wise to leave early), and (iii) the 'Adj. + of NP' construction (It was wise of John to leave early), which all involve three semantic components: (i) an individual a (John), (ii) a property P1 that describes a mental/behavioral propensity (wise), and (iii) another property P2 which typically describes an action (leave early). I argue that the three constructions share the meaning along the lines of: 'P2(a), and P2 is one of the properties that are expected to be true of any x such that P1(x)', while they differ as to which component they assert/pressupose. I further demonstrate that this analysis allows us to solve two known semantic puzzles concerning these constructions, the "entailement puzzle" and the "embeddability puzzle".